Perception of Men's Beauty and Attractiveness by Women with Low Sexual Desire. (15th December 2014) - Ferdenzi, Camille; Delplanque, Sylvain; Vorontsova‐Wenger, Olga; Pool, Eva; Bianchi‐Demicheli, Francesco; Sander, David
Abstract Introduction Despite the high prevalence of hypoactive sexual desire disorder (HSDD), especially among women, this sexual disorder remains poorly understood. Among the multiple factors possibly involved in HSDD, particularities in the cognitive evaluations of social stimuli need to be better characterized. Especially, beauty and attractiveness judgments, two dimensions of interpersonal perception that are related but differ on their underlying motivational aspects, may vary according to the level of sexual desire. Aim The main goal of this study was to investigate whether women with and without HSDD differ in their evaluations of beauty and attractiveness of men's faces and voices. Methods Young women from the general population (controls, n = 16) and with HSDD (patients, n = 16) took part in the study. They were presented with a series of neutral/nonerotic voices and faces of young men from the GEneva Faces And Voices database. Main Outcome Measures Ratings of beauty (i.e., assessments of aesthetic pleasure) and of attractiveness (i.e., assessments of the personal propensity to feel attracted to someone) and the frequency to which the participants pressed a key to see or listen to each stimulus again were the main outcome measures. Results Ratings of attractiveness were lower than ratings of beauty in both groups of women. The dissociation between beauty and attractiveness was larger in women with HSDD than in control participants. Patients gave lower attractiveness ratings than the controls and replayed the stimuli significantly less often. Conclusion These results suggest that women with HSDD are characterized by specific alterations of the motivational component of men's perception, very early in the process of interpersonal relationships. Our findings have significant implications, both in better understanding the specific cognitive processes underlying hypoactive sexual desire and more largely the evaluative processes involved in human mate choice. Ferdenzi C, Delplanque S, Vorontsova‐Wenger O, Pool E, Bianchi‐Demicheli F, and Sander D. Perception of men's beauty and attractiveness by women with low sexual desire. J Sex Med 2015;12:946–955.